Pengaruh Desain Produk dan Promosi Digital terhadap Keputusan Pembelian melalui Pembelian Implusif sebagai Variabel Mediasi pada Konsumen Tiktok Shop: Studi Kasus Mahasiswa Yogyakarta - Diki Ramadhan; Henny Welsa; Diansepti Maharani, Bernadetta (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the influence of product design and digital promotions on the purchasing decisions of TikTok shop consumers and to determine the influence of product design and digital promotions on the impulsive purchases of TikTok shop consumers. This research uses quantitative or survey research methods, a purposive sampling technique, where the sample for this research was taken from 112 respondents from Yogyakarta students who had made purchases at the TikTok shop. To test data quality, use validity and reliability tests. Classic assumption test, normality test, heteroscedasticity test, multicollinearity test and data analysis techniques using multiple regression analysis tests and hypothesis testing using partial tests (T test), coefficient of determination (R2) and Sobel test. The research results show that the product design variable (X1) does not significantly influence purchasing decisions (Y). Digital promotions (X2) have a positive and significant effect on purchasing decisions (Y). Product design (X1) has a positive and significant effect on impulsive purchasing (Z). Digital promotions (X2) have a positive and significant effect on impulsive purchases (Z). Impulsive buying (Z) has a positive and significant effect on purchasing decisions (Y).